When Do They Say Yes? An Analysis of the Willingness to Offer and Accept Mediation in Civil Wars. - Michael Greig, J.; Regan, Patrick M. (International Studies Quarterly, 2008)
Facilitating peace settlements among parties to a civil war represents a key challenge for policymakers. In spite of the grave consequences and relatively high frequency of civil wars, we know little about how best to manage them. In this article we examine the linked questions of under what conditions third parties provide and warring parties accept offers of mediation in civil wars. Our analysis suggests that third-party offers are closely tied to the interests a third party has in a civil war state as well as the historical ties between the third party and civil war state. Importantly, we note critical distinctions between the conditions that encourage offers of mediation from those that foster its acceptance. The theoretical and policy implications of knowing when to offer and the conditions under which an offer will be accepted could have dramatic effects on civil war termination.